Gaya Bahasa Kiasan Tokoh Betsuyaku Hiroka pada Film Ryū to Sobakasu no Hime - Dewi, Ni Kadek Annora; Meidariani, Ni Wayan (Japanese Literature Study Program, Faculty of Letters, Dr. Soetomo University, 2024)
This study aims to analyze the use of figurative language styles by the character Betsuyaku Hiroka in the film Ryū to Sobakasu no Hime by Mamoru Hosoda. Data collection in this study used the observation method. The method used in this study is a qualitative descriptive method using note-taking techniques. The theory used in this study is Gorys Keraf's theory of language style. The source of this study is the film Ryū to Sobakasu no Hime by Mamoru Hosoda which has 2 hours 1 minute 15 seconds duration. The results of this study show that there are 5 types of figurative language styles used by the character Betsuyaku Hiroka, including 1) Equation or simile, 2) Irony, 3) Cynicism, 4) Sarcasm, 5) Inuendo. The form of figurative language that is most often used by the character Betsuyaku Hiroka is cynicism. The use of cynical figurative language to demean, criticize or make fun of the physical, attitude and thoughts of the interlocutor. Keywords: figurative; film; language style; stylistics.